Nanoconfinement of the Low‐Temperature Dark Conglomerate: Structural Control from Focal Conics to Helical Nanofilaments. Issue 31 (8th May 2019) - Foley, Lee; Park, Wongi; Yang, Minyong; Carlson, Eric; Korblova, Eva; Yoon, Dong Ki; Walba, David M.
Abstract: The helical nanofilament (HNF) and low‐temperature dark conglomerate (DC) liquid‐crystal (LC) phases of bent‐core molecules show the same local layer structure but present different bulk morphologies. The DC phase is characterized by the formation of nanoscale toric focal conics, whereas the HNF phase is constructed of bundles of twisted layers. Although the local layer structure is similar in both phases, materials that form these phases tend to form one morphology in preference to the other. Targeted control of the nanostructures would provide pathways to potential applications and insight into how conditions drive a specific phase formation. Here, W624, a compound known to form the DC phase is confined in nanometer scale channels of porous anodized aluminum oxide (AAO) membranes. Within each nanochannel, the DC phase is suppressed forming the HNF structure instead, indicating the nanoscale spatial limitation can control the phase structure of the DC phase. Abstract : Nanoconfinement of the low‐temperature dark conglomerate phase of bent‐core liquid crystals in porous anodized aluminium oxide membranes results in a change in the phase morphology. The bulk sponge‐like structure of the phase is forced to adopt a helical structure under these conditions.